(x-y)[(x+y)^2-xy]+(x-y)[(x-y)^2+xy]

来源:学生作业帮助网 编辑:作业帮 时间:2022/11/29 16:09:25
(x-y)[(x+y)^2-xy]+(x-y)[(x-y)^2+xy]

(x-y)[(x+y)^2-xy]+(x-y)[(x-y)^2+xy]


原式
=(x-y)[(x+y)²-xy+(x-y)²+xy]
=(x-y)[(x+y)²+(x-y)²]
=(x-y)(x²+2xy+y²+x²-2xy+y²)
=(x-y)(2x²+2y²)
=2(x-y)(x²+y²)

解:原式=(x-y)[(x+y)^2-xy+(x-y)^2+xy]=(x-y)(2x^2+2y^2)=2(x-y)(x^2+y^2)


原式
=(x-y)[(x+y)²-xy+(x-y)²+xy]
=(x-y)[(x+y)²+(x-y)²]
=(x-y)(x²+2xy+y²+x²-2xy+y²)
=(x-y)(2x²+2y²)
=2(x-y)(x²+y²)为什么...

全部展开


原式
=(x-y)[(x+y)²-xy+(x-y)²+xy]
=(x-y)[(x+y)²+(x-y)²]
=(x-y)(x²+2xy+y²+x²-2xy+y²)
=(x-y)(2x²+2y²)
=2(x-y)(x²+y²)

收起